Mutant alleles of Schizosaccharomyces pombe rad9(+) alter hydroxyurea resistance, radioresistance and checkpoint control - Hang, Haiying (Oxford University Press, 2000)
Schizosaccharomyces pombe rad9 mutations can render cells sensitive to hydroxyurea (HU), gamma-rays and UV light and eliminate associated checkpoint controls. In vitro mutagenesis was performed on S.pombe rad9 and altered alleles were transplaced into the genome to ascertain the functional significance of five groups of evolutionarily conserved amino acids. Most targeted regions were changed to alanines, whereas rad9-S3 encodes a protein devoid of 22 amino acids normally present in yeast but absent from mammalian Rad9 proteins. We examined whether these rad9 alleles confer radiation and HU sensitivity and whether the sensitivities correlate with checkpoint control deficiencies. One rad9 mutant allele was fully active, whereas four others demonstrated partial loss of function. rad9-S1, which contains alterations in a BH3-like domain, conferred HU resistance but increased sensitivity to gamma-rays and UV light, without affecting checkpoint controls. rad9-S2 reduced gamma-ray sensitivity marginally, without altering other phenotypes. Two alleles, rad9-S4 and rad9-S5, reduced HU sensitivity, radiosensitivity and caused aberrant checkpoint function. HU-induced checkpoint control could not be uncoupled from drug resistance. These results establish unique as well as overlapping functional domains within Rad9p and provide evidence that requirements of the protein for promoting resistance to radiation and HU are not identical.